2022
DOI: 10.3389/fpsyg.2022.668276
|View full text |Cite
|
Sign up to set email alerts
|

Native Word Order Processing Is Not Uniform: An ERP Study of Verb-Second Word Order

Abstract: Studies of native syntactic processing often target phrase structure violations that do not occur in natural production. In contrast, this study examines how variation in basic word order is processed, looking specifically at structures traditionally labelled as violations but that do occur naturally. We examined Swedish verb-second (V2) and verb-third (V3) word order processing in adult native Swedish speakers, manipulating sentence-initial adverbials (temporal idag ‘today’, spatial hemma ‘at home’ and senten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…This suggests that the degree of acceptability for non-standard variation has consequences for the reactions seen in the eye-tracking record. Similarly, Sayehli et al (2022) suggested, based on their EEG study, that V3 after kanske 'maybe' (which is a more acceptable construction) was processed differently than V3 after other adverbials.…”
Section: Effects Of V3a Prominent Anomalymentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the degree of acceptability for non-standard variation has consequences for the reactions seen in the eye-tracking record. Similarly, Sayehli et al (2022) suggested, based on their EEG study, that V3 after kanske 'maybe' (which is a more acceptable construction) was processed differently than V3 after other adverbials.…”
Section: Effects Of V3a Prominent Anomalymentioning
confidence: 99%
“…Processing of V3evidence from EEG Three studies on Swedish have examined online processing of ungrammatical V3 after sentence-initial adverbials, measured by event-related potentials (ERPs) (Andersson et al, 2019;Yeaton, 2019;Sayehli et al, 2022). Andersson et al and Yeaton manipulated the order of subject and verb, as shown in (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation